Pemanfaatan Notifikasi Telegram Untuk Monitoring Perangkat CCTV Rumah Sakit Orthopaedi Purwokerto - Nalakhudin, Khaidir; Imron, Mohammad; Wiedanto Prasetyo, Muhamad Awiet (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
Security is one of the most important factors in an institution or company. By utilizing CCTV (Closed Circuit Television) technology, it can facilitate security, monitoring, and access to information in certain areas. The problem that often occurs is the lack of monitoring of the device which is not carried out for 24 hours. CCTV surveillance by technicians only runs for 14 hours, from 8 am to 10 pm, which means that outside these hours there is no CCTV surveillance. Therefore, it is necessary to have efforts to monitor CCTV devices if there are obstacles that cause the device to not work optimally. This study aims to create a CCTV device monitor system with problems using Telegram Bot notifications in real time and assist technicians in monitoring and maintaining CCTV devices, then indirectly helping companies achieve KPI targets and supervising employee performance.